The new generation Z in Asia : dynamics, differences, digitalization - Gentina, Elodie; Parry, Emma (Changing context of managing people., 2020)
This book is the first to compare the Asiatic Generation Z (born 1990-1995) in terms of country and culture specific drivers and characteristics based on interdisciplinary and international scientific research. Although Asia has been the focus of many articles and books on demographics, politics and economics, few authors understand in depth the behaviour of the young people in their roles as consumers and as new members of the working world. The New Generation Z in Asia: Dynamics, Differences, Digitalization explores how specific Asiatic cultures translate into a creative and innovative society in order to conduct business to adjust their recruitment and retention strategies, also examining how they attract and retain the best young talent in Asia. Written for academics and professionals in the fields of Management, Organizational Behaviour, Marketing, and Human Resource Management, this work examines a set of topics that describe societal and managerial feelings, goals, concerns and behaviours of a vast continent that stretches from East Asia through South Asia, Southeast Asia to Western Asia.